2010
DOI: 10.1371/journal.pone.0011864
|View full text |Cite
|
Sign up to set email alerts
|

Time Spent for Activation of Non-Profit Studies in Oncology in Italy

Abstract: AimThe aim of this paper is to describe the time spent to activate oncological non-profit clinical trials promoted in Italy by the National Cancer Institute of Naples, following the implementation of recent European laws.MethodologyData about the process of activation of 5 non-profit multicentre clinical trials were prospectively collected through a web-based system. The impact of European guidelines was assessed by comparing the efficiency of the process between applications started before and after the decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Although specific populations (eg, phase 3 oncology trials) have been studied in depth, such studies have not hitherto been attempted in broader populations that cross therapeutic areas and center-specific processes. 1321 Thus, the broad scope of the present study allowed us to identify several critical elements that contribute significantly to SSU time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although specific populations (eg, phase 3 oncology trials) have been studied in depth, such studies have not hitherto been attempted in broader populations that cross therapeutic areas and center-specific processes. 1321 Thus, the broad scope of the present study allowed us to identify several critical elements that contribute significantly to SSU time.…”
Section: Discussionmentioning
confidence: 99%
“…Various research articles have explored factors affecting SSU time. [13][14][15][16][17][18][19][20][21] Dilts and colleagues [15][16][17][18][19] examined SSU for cooperative groups involved in oncology trials, rigorously identifying hundreds of distinct processes and working steps and the subsequent decision points, processing loops, and stopping points between concept initiation and trial activation. In a recent publication, Dilts et al 19 noted that improvements to both the quality of the processes and to the time required to develop clinical trials should be made collaboratively and not in isolation.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the introduction of the so-called CTA form did not shorten time for administrative authorisation 6. Again, structural solutions should be considered, for example inclusion of administrative representatives within IECs who can sign contracts immediately IEC approval is granted 12.…”
Section: Discussionmentioning
confidence: 99%
“…Time to trial activation is critical for clinical research. Therefore, major efforts should be made to reduce and standardize procedures concerning the approval of clinical trials [9] .…”
Section: Introductionmentioning
confidence: 99%